Shenfu injection: a review of pharmacological effects on cardiovascular diseases - Xu, Fei-Fei; Xie, Xiao-Fang; Hu, Hai-Yan; Tong, Rong-Sheng; Peng, Cheng (Frontiers in Pharmacology, 2024)
Shenfu injection (SFI), composed of ginseng and aconite, is a Chinese patent developed from the classic traditional prescription Shenfu Decoction created more than 700 years ago. SFI has been widely used in China for over 30 years for treating cardiovascular diseases. The main components in it include ginsenosides and aconitum alkaloids. In recent years, the role of SFI in the treatment of cardiovascular diseases has attracted much attention. The pharmacological effects and therapeutic applications of SFI in cardiovascular diseases are summarized here, highlighting pharmacological features and potential mechanisms developments, confirming that SFI can play a role in multiple ways and is a promising drug for treating cardiovascular diseases. 1 Introduction Cardiovascular diseases (CVDs) remain the predominant cause of mortality and morbidity worldwide over the past 20 years, including atherosclerosis, coronary heart disease, arrhythmia, hypertension, cardiomyopathy, stroke and heart failure (Benjamin